Dc - dc charge controller for a small pv system - Mohammed Firdaus, Ramli (2016)
Nowadays, renewable energy such as solar power has become important to generate electricity and the solar power system can be installed at homes. In conjunction with the aforementioned points, solar power system is continuously improved by researchers around the world, who focused to attain the best design, in order to maximize the efficiency of solar power system. In this project, battery charging controller has been integrated and implemented towards the small scale solar panel system to achieve the best battery charging applications. This project utilized a battery charging in the form of intelligent controller method. The hardware system includes of Arduino UNO microcontroller as a main controller and temperature sensor (LM35) for sensing the maximum intensity of humidity. Initially, the application of the battery that is charged by the solar panel needs a battery charging controller so that it can control the battery from exceeding the maximum charging and discharging level to protect the battery from get damage. As in solar power system, charge controller is the heart of the system and design to protect the rechargeable battery. Apart from that, the energy from the battery can be used to drive a small load which is connected to the solar panel. The amount of the energy input generates by the PV panel is regarding to the weather. In conclusion, the application of the charge controller system delivers a convenient output power for a 12 volt system.